2017
DOI: 10.1007/s13346-017-0439-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential treatment of atopic dermatitis: tolerability and safety of cream containing nanoparticles loaded with hydrocortisone and hydroxytyrosol in human subjects

Abstract: Hydrocortisone (HC), topical glucocorticoid along with hydroxytyrosol (HT), and anti-microbial- and anti-oxidant-loaded chitosan nanoparticles (CSNPs) were prepared in large scale and analyzed for their adverse effects on healthy human skin followed by repeated applications. Ten subjects were randomized to receive test (HC-HT CSNPs) and vehicle samples (aqueous (AQ) cream). They were applied on the arms for 28 days, and transepidermal water loss (TEWL), erythema intensity, and irritation score were measured. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 35 publications
2
28
0
1
Order By: Relevance
“…By demonstrating that EVOO phenols exert anti‐inflammatory effects on human keratinocytes, our study not only extends these previous findings to also encompass HTy‐Ac, but it shows that human keratinocytes are direct targets of EVOO phenols, which appears translationally interesting in the context of inflammatory skin disorders, as also encouraged by the mentioned studies investigating the potential use of olive oil‐derived compounds in the field of dermatology …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…By demonstrating that EVOO phenols exert anti‐inflammatory effects on human keratinocytes, our study not only extends these previous findings to also encompass HTy‐Ac, but it shows that human keratinocytes are direct targets of EVOO phenols, which appears translationally interesting in the context of inflammatory skin disorders, as also encouraged by the mentioned studies investigating the potential use of olive oil‐derived compounds in the field of dermatology …”
Section: Discussionsupporting
confidence: 82%
“…In a mouse model of AD, HTy had beneficial effects, reducing erythema intensity and dermatitis and decreasing T‐helper cell cytokines in serum and skin, albeit only in the presence of hydrocortisone . Recently, a study evaluated the safety of a cream with hydrocortisone and HTy, showing that long‐term use had a favorable safety profile, a finding encouraging further clinical trials …”
Section: Discussionmentioning
confidence: 99%
“…Siddique et al loaded hydrocortisone and hydroxytyrosol—a glucocorticoid for topical application, and an antioxidant molecule, respectively, in chitosan NPs, which were then formulated in an aqueous cream [86]. The authors reported no systemic effects of the drugs nor toxicity, with enhanced safety and tolerability of the developed cream.…”
Section: Nanoparticles For Atopic Dermatitismentioning
confidence: 99%
“…Siddique and coauthors [[39], [40], [41]] exploited nanoparticles for a targeted delivery of systemic corticosteroids at the inflammation site. In a murine model, topically applied cationic polymeric chitosan-based nanoparticles (CSNPs) loaded with anti-inflammatory hydrocortisone and antimicrobial hydroxytyrosol (HC-HT-CSNPs, size of 228.5 ± 7 nm and positive surface charge of 39±5 mV) displayed optimal epidermal and dermal permeation, reaching the deepest skin layers with an efficiency 2.46-fold higher with respect to the commercial reference formulation.…”
Section: Atopic Dermatitis Nanoparticles and Nanocarriersmentioning
confidence: 99%